2019
DOI: 10.1371/journal.pone.0223357
|View full text |Cite
|
Sign up to set email alerts
|

Understanding variation in health service coverage and maternal health outcomes among districts in Rwanda – A qualitative study of local health workers’ perceptions

Abstract: ObjectiveTo obtain the perspectives of health professionals and community health workers on factors that determine health service coverage and maternal health outcomes so as to understand variations between districts.Methods16 Focus group discussions involving four different groups of participants were conducted in May 2015 in four purposively selected districts, complemented by three key informant interviews in one of the districts.ResultsThe solidarity support for poor people and the interconnectedness betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Respondents said that the CT induces additional workload, which is sometimes difficult to manage. Excessive workload among health workers has been documented in different contexts as affecting the quality of health services ( 19 21 ). A review of the CT forms involving staff at operational and programmatic levels can support shortening of the forms and their harmonization with existing routine forms.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents said that the CT induces additional workload, which is sometimes difficult to manage. Excessive workload among health workers has been documented in different contexts as affecting the quality of health services ( 19 21 ). A review of the CT forms involving staff at operational and programmatic levels can support shortening of the forms and their harmonization with existing routine forms.…”
Section: Discussionmentioning
confidence: 99%
“…These NGOs focused mainly on maternal and newborn care, worked closely with the ministry of health (MOH) and provided highly effective support that included; direct care provision, ensuring adequate and qualified staff, infrastructure development, robust quality improvement mechanisms and financial and technical assistance to support clinical innovation areas [14,15]. Likewise, the smoother landscape found in eastern provinces compared to the northern region could be attributed to a higher likelihood of MCH service uptake because it enables for easier access to health facilities, as other studies have shown [54,55]. The odds of having CoC in the western region were less.…”
Section: Table 4 Factors Associated With Coc Utilizationmentioning
confidence: 99%